Presentation and physical therapy management of upper cervical instability in patients with symptomatic generalized joint hypermobility: International expert consensus recommendations - Russek, Leslie N.; Block, Nancy P.; Byrne, Elaine; Chalela, Susan; Chan, Cliffton; Comerford, Mark; Frost, Nicole; Hennessey, Sharon; McCarthy, Ann; Nicholson, Leslie L.; Parry, Jason; Simmonds, Jane; et al. (Frontiers in Medicine, 2023)
Experts in symptomatic generalized joint hypermobility (S-GJH) agree that upper cervical instability (UCI) needs to be better recognized in S-GJH, which commonly presents in the clinic as generalized hypermobility spectrum disorder and hypermobile Ehlers-Danlos syndrome. While mild UCI may be common, it can still be impactful; though considerably less common, severe UCI can potentially be debilitating. UCI includes both atlanto-occipital and atlantoaxial instability. In the absence of research or published literature describing validated tests or prediction rules, it is not clear what signs and symptoms are most important for diagnosis of UCI. Similarly, healthcare providers lack agreed-upon ways to screen and classify different types or severity of UCI and how to manage UCI in this population. Consequently, recognition and management of UCI in this population has likely been inconsistent and not based on the knowledge and skills of the most experienced clinicians. The current work represents efforts of an international team of physical/physiotherapy clinicians and a S-GJH expert rheumatologist to develop expert consensus recommendations for screening, assessing, and managing patients with UCI associated with S-GJH. Hopefully these recommendations can improve overall recognition and care for this population by combining expertise from physical/physiotherapy clinicians and researchers spanning three continents. These recommendations may also stimulate more research into recognition and conservative care for this complex condition.